Тастамбек Қ.Т., Акимбеков Н.Ш., Цяо Сяохуэй, Бердіқұлов Б.Т., Жұбанова А.А. Қоңыр көмір негізінде жоғары сапалы түтінсіз және күлділігі аз брикет алудың биотехнологиялық аспектілері: Әл-Фараби атындағы Қазақ ұлттық университеті, Қазақстан, Алматы қ., *е-mail: tastambeku@gmail.com (Eurasian Journal of Ecology, 2018)
Biotechnological processes of coal processing, including transformation and conversion can beaimed at obtaining various solid, liquid and gaseous fuels and products from it, as well as improving itstechnical and consumer characteristics. Combusted in the municipal and industrial sectors, coal fuel,which has a low sulfur content, low smoke, reduced ash content and the required structural-granulometric composition, is combined under the name «smokeless fuel» or «briquettes».Also, the main areas of coal processing based on the use of native or genetically modified microorganisms is to improve their functional and environmental characteristics for energy-engineering applications by removing mustard and organic sulfur. When developing biotechnological approaches, variousgroups of bacteria and fungi are used, and the processes can be performed both in mesophilic and thermophilic conditions in the presence of oxygen. At present, new biotechnological methods are being developed based on the removal of sulfur fromcoal, i.e. biodesulfurization is one of the processes that causes the greatest interest. Natural biodesulfurization process involves microbial ecosystems and biocenoses, which include symbiotic commensalmicroorganisms.For the reasons listed above, the study and creation of new efficient technologies for the productionof solid fuels, including smokeless, is a timely solution to the current problem.Key words: coal, microorganism, biosolubilization, desulfurization, smokeless fuel.